Performance Analysis of LoRaWAN on AU915 Frequency Band for Ambience Monitoring System in Brazil - Carvalho, Dhiego Fernandes [UNESP] (2024)
LoRaWAN, a globally utilized LPWAN technology, is predominantly studied and deployed within the European EU868 (868 MHz) and USA US915 (915 MHz) frequency bands, with a vast amount of literature documenting its applications in these regions. However, there is a noticeable gap in research concerning other frequency bands, such as the Australian AU915, which is also utilized in Brazil. This paper aims to explore the characteristics of the AU915 frequency band in Brazil, and how it can affect the performance of an ambience monitoring system application. The study not only focuses on LoRaWAN metrics within the AU915 frequency band but also reveals the practical implications of its unique characteristics. The experiments analyze architectural delays and success rates across various Data Rates (DR) for uplink and downlink messages at different distances, considering the absence of uplink dwell time restrictions. The results demonstrate that, in ambient monitoring systems, different data rates (DRs) significantly influence transmission delays. Additionally, the Uplink Dwell Time restriction eliminates the use of DR0 and DR1 rates, and restricts DR2 in applications using LoRaWAN AU915 in Brazil, directly impacting the success rate of transmissions and, consequently, its network coverage.